Investment Decision Factors - Sugiarto, Sugiarto; Surahman, Dedy; Sya’ban, Ma’ruf (UMSurabaya Publishing, 2023)
The purpose of this study was to determine the effect of financial literacy and personal income on investment decisions. Data collection was carried out by survey using a questionnaire given to 75 respondents. The results of this study indicate that Financial Literacy partially has no significant effect on Financial Behaviour, Financial Literacy partially has a significant effect on Investing Decisions, Personal Income partially has no significant effect on Financial Behaviour, Personal Income partially has a significant effect on Investing Decisions, Financial Behaviour partially has no significant effect on Investing Decisions.